Effectiveness of sales manager's leadership in implementing lead management: A case study on Tan Chong Motors (Sarawak) - Ooi, Chin Lye (2015)
The mission of Tan Chong Motors (TCM) Sarawak was to fulfill top management’s vision for Sarawak Region Mid-Term Plan of increasing the current market share of 3.6% (for year 2011) to 24.4% by 2016. The sales management and leadership behaviors of present Heads of Branch (HOBs) were found to be ineffective, especially in managing and leading the sales teams to achieve the mid-term goal by Year 2016. The aim of this research was to examine factors influencing HOBs’ leadership in implementing lead management in Tan Chong Motors (TCM) Sarawak region. Hence, the major focus of this study was to examine the effectiveness of HOBs’ leadership behaviors and sales management approaches in the branch sales operation in Sarawak Region. For this purpose, an action research (AR) embedded within the conceptual framework was conducted in three cycles involving; formative evaluation, application and implementation of change by Tan Chong Motors Sarawak Region and TCM Head Quarter (HQ). Process, impact and outcome evaluation data was obtained from quantitative and a combination of qualitative approaches namely; structured interviews, participant’s observations, archival search, focus group discussion and critical incident technique. The participants of this study were HOBs of the five branches in TCM Sarawak Region. Survey was also conducted on 62 sales advisors from the respective branch. The study found that inadequacy of leadership behaviors and lack of management knowledge, lack of structured management control processes, lack of clear job scope and an inefficient Lead Management Information System were the main reasons contributing to the leadership ineffectiveness in implementation lead management in TCM Sarawak Region. With the findings of this AR, TCM HQ has adopted and standardized the four proposals made, namely to adopt farming approach of selling, to enhance Lead Management Information System, to standardize HOBs’ job scope and, to provide structured training program for all TCM HOBs